Sickle Cell-Related Complications in Patients Undergoing Cardiopulmonary Bypass. Issue 5 (September 2020) - Chacon-Portillo, Martin A.; Mossad, Emad B.; Zea-Vera, Rodrigo; Beckerman, Ziv; Binsalamah, Ziyad M.; Adachi, Iki; Mery, Carlos M.; Imamura, Michiaki; Heinle, Jeffrey S.; Fraser, Charles D.
Background: We aimed to describe our experience with patients with sickle cell trait (SCT) and undergoing surgery on cardiopulmonary bypass (CPB). Methods: Data on all patients with SCT or sickle-α thalassemia who underwent surgery on CPB were collected (1996-2017). Results: Overall, 46 patients were included, 37 (80%) had SCT and 9 (20%) had sickle-α thalassemia. A total of 4 (9%) developed a potential sickle cell–related complication. Patients with sickle cell-related complications were significantly older (median 14 years vs 14 months, P = .037) and heavier (median 54 kg vs 9 kg, P = .041). Complications occurred, although without statistical significance, in patients who underwent longer median CPB times (249 minutes vs 137 minutes, P = .069), lower median temperature (31.7 °C vs 33.3 °C, P = .094), and a higher percentage underwent deep hypothermic circulatory arrest (50% vs 7%, P = .053). A total of 30 (65%) patients underwent exchange transfusion (ET) pre-bypass. Patients who underwent ET were significantly older (median 4 years vs 7 months, P = .003) and heavier (median 16 kg vs 6 kg, P = .015) than patients who did not undergo ET. The incidence of complications was comparable between patients who underwent ET (10%) and those who did not (6%). Conclusions: In this retrospective, single-center study, it has been shown that cardiac surgery requiring CPB in patients with SCT and sickle-α thalassemia had a low risk for sickle cell-associated complications. In this cohort of patients, older age, longer CPB times, lower median temperature, and the utilization of deep hypothermic circulatory arrest appear to play an important role in the development of complications.